Luteolin attenuates PM2.5-induced inflammatory responses by augmenting HO-1 and JAK-STAT expression in murine alveolar macrophages - Hsieh, Wen-Che; Lai, Chane-Yu; Lin, Hui-Wen; Tu, Dom-Gene; Shen, Ting-Jing; Lee, Yi-Ju; Hsieh, Ming-Chang; Chen, Ching-Chung; Han, Hsin-Hsuan; Chang, Yuan-Yen (Food and agricultural immunology, 2022)
To explore the involved mechanisms and possible treatments of ambient PM2.5 exposure-induced lung inflammation, this work studied the activity of luteolin, a natural flavonoid which widely presents in many plant species, in murine alveolar macrophage MH S cells exposed to PM2.5. Results showed PM2.5 induced an inflammatory response, as evidenced by significantly increased TNF-α, IL-6, MCP-1 and Rantes levels. and induced iNOS, COX-2, and NF-κB protein expressions in MH-S cells. Moreover, luteolin pre-treatment reduced JAK2 and STAT1 but not STAT3 protein expressions in PM2.5-stimulated MH-S cells. Performing JAK2 inhibitor AG490 further showed reduced TNF-α and IL-6 productions as well as iNOS, COX-2, and NF-κB protein expressions. In addition, although PM2.5 exposure could elevate HO-1 expression basically, luteolin pre-treatment and AG490 administration further significantly enhanced HO-1 expression additionally. Collectively, these results revealed that luteolin inhibits inflammation through suppressing JAK2/STAT1/NF-κB pathway and enhancing HO-1 expression in PM2.5-challenged alveolar macrophage MH-S cells.